2008
DOI: 10.1073/pnas.0808903105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myosin-binding protein C decorates F-actin: Implications for cardiac function

Abstract: Cardiac myosin-binding protein C (cMyBP-C) is an accessory protein of striated muscle sarcomeres that is vital for maintaining regular heart function. Its 4 N-terminal regulatory domains, C0-C1-m-C2 (C0C2), influence actin and myosin interactions, the basic contractile proteins of muscle. Using neutron contrast variation data, we have determined that C0C2 forms a repeating assembly with filamentous actin, where the C0 and C1 domains of C0C2 attach near the DNase I-binding loop and subdomain 1 of adjacent actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
140
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 41 publications
(43 reference statements)
13
140
0
1
Order By: Relevance
“…Remarkably, we discovered that all 3 truncated forms of recombinant cMyBP-C studied have dramatically different phosphorylation states even with a seemingly minor truncation compared with the full-length protein. Truncated recombinant proteins are routinely used to substitute the fulllength forms in crystal structure (46) and functional studies (47). Our study provides direct evidence of alterations in posttranslational states between truncated and full-length recombinant proteins, which can lead to variations in their structure and function.…”
mentioning
confidence: 89%
“…Remarkably, we discovered that all 3 truncated forms of recombinant cMyBP-C studied have dramatically different phosphorylation states even with a seemingly minor truncation compared with the full-length protein. Truncated recombinant proteins are routinely used to substitute the fulllength forms in crystal structure (46) and functional studies (47). Our study provides direct evidence of alterations in posttranslational states between truncated and full-length recombinant proteins, which can lead to variations in their structure and function.…”
mentioning
confidence: 89%
“…The structural parameters derived from SAXS also indicated that it is possible for the N-terminal domains to reach across the interfilament space and interact with actin. Subsequent SANS 81 with contrast variation studies of the assembly formed between actin and deuterated C0C2 showed that the N-terminal domains of cMyBP-C promote filamentous actin (F-actin) assembly and decorate actin filaments in a regular fashion. The length of the average C0C2/F-actin assembly exceeded the size limit that could be determined from the SANS data (a limit determined by the minimum q-value measured) so cross-sectional structural analysis was pursued.…”
mentioning
confidence: 99%
“…81 (A) An example of the pair-distance distribution profiles of cross-section P c (r) calculated from scattering data at the solvent match points of cMyBP-C 2 H-C0C2 ($ 100% 2 H 2 O) and F-actin ($ 40% 2 H 2 O) within the macromolecular assembly in comparison with the P c (r) of undecorated F-actin. The P c (r) shows the characteristic peaks with relative intensities as expected for an extended four domain structure; the first, second, third, and forth peaks correspond to atom-pair distances within a single domain, a pair of neighboring domains, domains separated by one domain, and domains separated by two domains.…”
mentioning
confidence: 99%
“…On activation, Tn binds Ca 2+ , causing Tm to move onto actin SD3 (the "closed" position), exposing myosin binding sites on SD1 and initiating crossbridge cycling and contraction (29)(30)(31)(32)(33)(34)(35). When a model of Tm in its low Ca 2+ (blocked) state is positioned on the reconstruction of F-actin decorated with C0C3, it appears to clash with cMyBP-C's C0 and C1 domains, suggesting that cMyBP-C and Tm might compete for binding to SD1 in the relaxed thin filament (25,27,28). As a consequence, cMyBP-C might be expected to activate the thin filament by physically preventing Tm from assuming its blocked position (25,27,28).…”
mentioning
confidence: 99%
“…Neutron scattering and NMR titration analysis of F-actin decorated with the N-terminal fragment C0C2 (Fig. 1) suggested that C0C2 binds to subdomain 1 (SD1) and the DNase loop of actin (25) via key regions within C0 and C1 (10). More direct observations by negative stain electron microscopy (26) and 3D reconstruction (27) suggest that C0 and C1 bind to SD1 of actin, whereas the M domain crosses Significance Myosin-binding protein C (MyBP-C) is a component of myosin filaments, one of the two sets of contractile elements whose relative sliding is the basis of muscle contraction.…”
mentioning
confidence: 99%